Tending the Digital Commons: A Small Ethics toward the Future. - Jacobs, Alan (Hedgehog Review)
The article focuses on ethics toward the future and social media presence was a natural one and interested in and fairly knowledgeable about computing. It mentions vulnerability raises wide-ranging questions that ought to be of general concern and online are not faced here simply with matters of intellectual property. It also mentions technology in an intriguing and important book "The Imperative of Responsibility".